Inheritance, QTLs, and Candidate Genes of Lint Percentage in Upland Cotton - Niu, Hao; Ge, Qun; Shang, Haihong; Yuan, Youlu (Frontiers in Genetics, 2022)
Cotton (Gossypium spp.) is a kind of important nature fiber plants. Lint percentage (LP) is one of the most important components of cotton yield. LP is a typical quantitative trait with high variation and heritability. Many cotton lint percent genetic linkage and association maps have been reported. Based on the results have been reported, the inheritance, quantitative trait loci (QTLs) and candidate genes of LP were systemically summarized. We analyzed these data to provide information for LP genetic study and molecular breeding. Currently, more than 1439 QTLs controlling LP have been reported. Excluding the replicate QTLs, more than 417 unique QTLs on 26 chromosomes for LP have been identified, including more than 243 QTLs identified at LOD > 3. Among them, more than 60 are stable, major effective QTLs which can be used in marker assisted selection (MAS). More than 90 candidate genes of QTLs for LP have been reported, they encode MYB, HOX, and NET like proteins, and so on, and most of them preferentially express during fiber initiation and elongation. A putative molecular regulatory model of LP was provided. These data will lay a foundation for the genetic study and molecular breeding of LP in future.